Antimicrobial Activity of Commercial Concrete Sealant Against Salmonella Spp: A Model for Poultry Processing Plants - Paiva, D.M.; Singh, M.; Macklin, K.S.; Price, S.B.; Hess, J.B.; Conner, D.E. (International Journal of Poultry Science, 2009)
Salmonella is an important foodborne pathogen often associated with poultry and highly prevalent in poultry processing plants. The objective of this study was to determine the efficacy of a commercial grade concrete sealant (BioSealed for ConcreteTM) to prevent bacterial attachment, colonization and antimicrobial effects against multiple strains of Salmonella (S. enteritidis, S. Kentucky, S. Typhimurium, S. Senftenberg and S. Heidelberg) on concrete blocks. Individual strains of Salmonella spp. were inoculated onto the concrete blocks and divided into 4 different treatment groups: (A) Bricks which were not treated with BioSealed for ConcreteTM (B) Bricks which were treated with BioSealed for ConcreteTM before inoculation (C) Bricks which were treated with BioSealed for ConcreteTM after inoculation and (D) Bricks which were treated with BioSealed for ConcreteTM before and after inoculation. External and internal surfaces of the treated concrete blocks were swabbed, serially diluted and plated onto XLD agar. Reductions of survival counts were enumerated and recorded as log10 CFU/cm2. Significantly (p<0.05) lower viable counts were observed following treatments C and D as compared to treatments A and B. However, no significant differences (p>0.05) in the survival populations of Salmonella were observed between treatments A and B for all five strains tested and between treatments C and D for any of the strains tested. This indicates that BioSealed for ConcreteTM proved to be a potent antimicrobial against multiple strains of Salmonella and can be used as an alternative method to control this pathogen in processing plant environments.